Determining the optimal insemination time of bitches (FAVE Sección Ciencias Veterinarias, 2022)
Nowadays, breeding dogs requires a competent, science-based approach. In particular, the choice of the optimal insemination time (both natural and artificial) is one of the important factors of successful mating or artificial insemination of bitches and is crucial in the problem of infertility. The period of fertilization (the time when ovicells can be fertilized) is 2-5 days after ovulation. Therefore, mating should be performed immediately before or during this period. The optimal time can be determied using various methods that estimate the period of fertility (when mating/inseminación can lead to conception). However, none of the diagnostic techniques is absolutely reliable, so for the most accurate result, it is recommended to use several (two or three) studies. For example: counting days, assessment of vulvar and vaginal discharge plus smear and/or vaginoscopy. Control mating increases the probability of conception and is usually performed the day after the first mating. It should be considered that the time of ovulation in the same bitch during different heat can be different. For bitches with problems of conception use the maximum number of methods with the analysis of past successful and unsuccessful matings. Choosing a specific method also implies an economic aspect, such as when owners have to carry bitches for a long distance and they need to be sure of the exact date of ovulation.